How can the shipping industry adopt a hybrid model : the case of Arista Shipping - Rodrigues, Amanda Mouzinho (2019)
This thesis discusses a stakeholder management and engagement case for Arista Shipping and its’ ambition to adopt a hybrid organisational model (Project Forward) by constructing, operating and commercialising Liquefied Natural Gas (LNG) fuelled vessels, formally called as Forward Vessels. With LNG being the most environmentally friendly option out there, Arista is committed to exceed the environmental regulation and to own the ‘cleanest’ fleet of vessel. Through deeper investigation of the methods of stakeholder engagement, this case study focuses on analysing critical stakeholders and complementing with most appropriate methods of engagement, with the objective of advancing the project. This analysis presents stakeholder management and engagement tools that allows managers to identify as well as map each individual stakeholder, thenceforth, accommodating most pertinent methods based on their interests, attributes and roles. For this specific case of Arista Shipping, the engagement methods are to be specifically analysed for: charterers, shipyards and investors/financiers.